Separating Poor Playmates: Untangling Commuter Rail from Freight. Issue 1 (January 2020) - Allen, John G.; Newmark, Gregory L.
North American commuter railroads run their trains largely on tracks shared with freights (and in the northeastern US, often shared with intercity passenger trains). This sharing makes commuter rail relatively affordable to implement. However, as freight traffic grows, so does the potential for delays. If freight and commuter operations affect each other's performance, it may be necessary to consider separation measures, not adding to the existing shared-track capacity. Temporal separation can work on low-volume operations. Busier lines may require physical separation, which can be implemented in several forms for trunk lines (grade separation at junctions, freight bypass, partial trunk line separation, and full trunk line separation), as well as physical separation in downtown areas. This article identifies these separation options, describes their attributes, presents representative examples, and outlines criteria for evaluation.